EFEKTIVITAS SURAT KEPUTUSAN GUBERNUR JAWA TENGAH NOMOR 800/09623 TENTANG KEDISIPLINAN TERHADAP KINERJA PEGAWAI NEGERI SIPIL DI SEKRETARIAT DAERAH PROVINSI JAWA TENGAH (STUDI KASUS PROGRAM KELUAR KANTOR BAWA KARTU) - Muhammad Ari Noviyanto; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Performance of Civil Servants in the Central Java Provincial Secretariat is expected to increase, especially related to the order and discipline of civil servants in carrying out working hours related to the performance of civil servants with the program out of office carry card in accordance with the Decree of Central Java Governor dated October 27, 2016 Number 800/09623 about Order and Discipline of civil servants. Some experts say that performance is influenced by discipline factors. Therefore this research uses the theory of public administration, human resource management, discipline, and performance. This research uses quantitative method which involves 83 respondents namely PNS Setda of Central Java Province which is still active. Based on the results of the study, Discipline has a strong positive relationship with Performance. While in analyzing the influence, Discipline has an influence on the Performance of civil servants in the Regional Secretariat of Central Java that is equal to 47%. Recommendations that the authors provide that need to be improved back office program take the card, because the results of the study stated the program is effective.